2014
DOI: 10.1111/jawr.12219
|View full text |Cite
|
Sign up to set email alerts
|

Water and Sediment Quality in the Clinch River,Virginia andTennessee,USA, over Nearly Five Decades

Abstract: The Clinch River, in eastern United States, supports a diverse freshwater fauna including endangered mussels. Although mussel populations are stable in the Clinch's northeastern Tennessee segment, long-term declines have been documented upstream in Virginia. We analyzed water and sediment quality data collected by government agencies from the 1960s through 2013 in an effort to inform current management. The river was divided into sections considering data availability and major tributaries. We tested for spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(45 citation statements)
references
References 71 publications
(129 reference statements)
2
43
0
Order By: Relevance
“…Our findings for the Powell River are similar to what has been observed in the lower Clinch River, where mussel declines correspond temporally with increasing trends for DS, likely of mining origin, and where mussel status improves with distance from a primary miningorigin DS source: water influx to the Clinch by the Guest River Jones et al, 2014;Price et al, 2014;Zipper et al, 2014). This correspondence of observations for the two rivers adds urgency to the essential questions.…”
Section: Relationships Among Mining Water Quality and Mussel Declinessupporting
confidence: 88%
See 2 more Smart Citations
“…Our findings for the Powell River are similar to what has been observed in the lower Clinch River, where mussel declines correspond temporally with increasing trends for DS, likely of mining origin, and where mussel status improves with distance from a primary miningorigin DS source: water influx to the Clinch by the Guest River Jones et al, 2014;Price et al, 2014;Zipper et al, 2014). This correspondence of observations for the two rivers adds urgency to the essential questions.…”
Section: Relationships Among Mining Water Quality and Mussel Declinessupporting
confidence: 88%
“…the total mass of mining-disturbed materials exposed to environmental waters is influential. Price et al (2014) also noted increasing temporal trends for DS in the Clinch River, which is similarly influenced by Appalachian surface coal mining that has occurred continuously and progressively over a multi-decade study period.…”
Section: Water Qualitymentioning
confidence: 90%
See 1 more Smart Citation
“…Prior research has found spatial and temporal associations of elevated TDS concentrations with freshwater mussel declines in the Clinch River in Virginia (Johnson et al, 2014;Price et al, 2014), suggesting that elevated major ions may be causing toxicity in the Clinch River. This idea also applies to the Powell River, where TDS concentrations are substantially higher in the upper reaches of the river and mussel populations have experienced long-term declines at monitoring locations downstream of these high TDS reaches (Ahlstedt et al, 2005;Johnson et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…1). Long-term water quality monitoring of the Clinch and Powell Rivers has documented increasing temporal trends of TDS concentrations since the 1960s (Price et al, 2011(Price et al, , 2014. Independent biological monitoring, initiated in 1979, has documented significant declines of freshwater mussel richness and density in sections of Clinch River and throughout the Powell River (Ahlstedt et al, 2005;Johnson et al, 2012;Jones et al, 2014).…”
Section: Introductionmentioning
confidence: 96%